Analisis Kesulitan Pemahaman Matematika Materi Kelipatan dan Faktorisasi Bilangan di Kelas 5 Sekolah Dasar 1 Loram Kulon - Naila Anisah Nuri Candrawati; Lusy Rahmawati; Anggraini, Dian Mustika; Nadhifah , Ainun (Tarunateach: Journal of Elementary School, 2024)
This research explores the difficulty of understanding mathematics in multiples and number factorization material in grade 5 of the 1 Loram Kulon Elementary School. Qualitative research methods are used to achieve a holistic understanding of student problems. Data was collected through classroom observations and teacher interviews, involving grade 5 students as research participants. Data analysis uses qualitative analysis techniques. The research results revealed that the majority of students faced difficulties in internalizing the concepts of multiples and number factorization. Factors such as a lack of understanding of basic multiplication concepts, limited understanding of patterns, and difficulty applying concepts in real contexts are the main obstacles. This research not only identifies difficulties, but also proposes solutions by designing and implementing pedagogical interventions. The intervention involves a contextual learning approach, the use of learning media, and adjustments to teaching methods. The research results also showed a significant increase in students' understanding of multiples and number factorization material through pedagogical intervention.